Only the names remain : the Cherokees and the Trail of Tears - Bealer, Alex W.; Rodanas, Kristina (Boston : Little, Brown, 1996)
Tells the story of how the Cherokee nation was cheated out of its land in the Appalachian mountains of Georgia in the 1830s by white men and political leaders who refused to enforce the laws protecting Native-American rights, forcing the Cherokees to begin a treacherous journey to Arkansas which claimed many of their lives.
Wilson's Children
Voice of Youth Advocates (V.O.Y.A.)
Kirkus Review
7.3
3-6
Keywords: Cherokee Indians -- History -- 19th century -- Juvenile literature; Trail of Tears, 1838 -- Juvenile literature; Cherokee Indians -- Relocation -- Juvenile literature; Cherokee Indians -- History; Trail of Tears, 1838.; Indians of North America -- History; Cherokee Indians -- History; Trail of Tears, 1838.; Indians of North America -- History